Reductions in HIV Prevalence Rates among Substance-using Men Who Have Sex with Men in Los Angeles County, 2008–2011 - Reback, Cathy J. (AIDS Educ Prev, 2014)
An outreach program performed street encounters with 5,599 unique substance-using MSM from January 2008 through December 2011. HIV prevalence reduced from 20.2% in the first half of 2008 to 8.1% in the second half of 2011. Older, gay-identified, non-Hispanic/Latino participants were each more likely to report a HIV-positive serostatus. When controlling for these cofactors, robust log-Poisson analysis revealed that each additional day of methamphetamine (RRR=1.03; 95% CI=1.02–1.03) and/or marijuana (RRR=1.01; 95% CI=1.01–1.02) use in the previous 30 days, injection drug use at any point in their lifetime (RRR=2.01; 95% CI=1.70–2.37), and/or unprotected anal intercourse with another male in the previous 30 days (RRR=1.48; 95% CI=1.29–1.71) were associated HIV-positive status. When controlling for all these cofactors, the probability of reporting a HIV-positive status reduced an estimated 9% (95% CI: 6%–12%) every six months throughout the reporting period. Self-reported HIV prevalence decreased among this sample of substance-using MSM in LAC from 2008–2011.